“Temur Tuzuklari” - the basis of just state - Rustamaliyev, Mirjalol (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article discusses Amir tuzuklari, a product of Amir Temur's views on statehood and diplomacy, military, skills, creativepotential, science, art and architecture